Emergency nursing: the Institute of Hygiene's performance during the brazilian civil war of 1932 - Maria Cristina da Costa Marques; Danilo Fernandes Brasileiro; Felipe Daiko Fraga (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objectives: to analyze and describe the São Paulo Institute of Hygiene's performance, now the School of Public Health of the Universidade de São Paulo, in the training of emergency nurses during the Brazilian Civil War. Method: descriptive, historical-documentary study. Results: ministered from July 13 to August 31, 1932 to 383 students, in five classes, with an average of ten days of class. The discipline First Aid to the Wounded of Trenches is highlighted and was ministered by the nurse Iracema Niebler. At the end of the course, the students graduated and made up the List of Nurses of the Barracks Battalion of São Paulo. Conclusion and implications for the practice: the Institute of Hygiene's performance in the training of civilians in emergency/war nurses revealed the institutional political alignment with the revolutionary movement of 1932, as well as the historical rescue of one of the first initiatives to train hands-on nurses assist in emergency situations during the most emblematic brazilian Civil War of 1932.